Self-regulating naturally occurring microcapsules for controlled release of Levodopa - Hamad, Shwan Abdullah (Sulaimani Journal for Pure and Applied Sciences, 2019)
Levodopa remains the gold standard treatment for patients suffering with Parkinson’s disease. Patients can become sensitive to fluctuations in plasma concentration of the drug, resulting in devastating side effects. This present paper reports the encapsulation of LV into sporopollenin exine microcapsules prepared in-house from Lycopodium Clavatum plant. The loaded sporopollenin exine microcapsules were prepared by removing the cellulosic intine, and then filling the internal cavity surrounded by the sporopollenin exine with a concentrated solution of LV. The trapped drug was then precipitated inside the microcapsules using pH change, followed by a thorough washing. The released amount of the drug in aqueous media resembling physiological conditions of human blood plasma was then quantified using UV-Vis spectrophotometer. The results showed that LV can be successfully encapsulated within the sporopollenin exine microcapsules, and a sustained release of the drug can be achieved. This paper also shows that the microcapsules loaded with the drug can act as a self-regulating device to release the drug in aqueous medium over a longer period.
Keywords: Parkinsons disease; Levodopa LV; Microcapsules; Sporopollenin; Encapsulation; Controlled Release; selfregulating microcapsules